If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -13 = 4 + 11 Reorder the terms: -13 + 6t = 4 + 11 Combine like terms: 4 + 11 = 15 -13 + 6t = 15 Solving -13 + 6t = 15 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 6t = 15 + 13 Combine like terms: -13 + 13 = 0 0 + 6t = 15 + 13 6t = 15 + 13 Combine like terms: 15 + 13 = 28 6t = 28 Divide each side by '6'. t = 4.666666667 Simplifying t = 4.666666667
| 11x+8=7x+36 | | 4x+5(x-9)=0 | | 13t-11=6+4 | | 6x+12=108-6x | | x+14=8(x+7) | | x+14=8(x+6) | | 0.5x^2-x-0.25=0 | | -30n=-27n-12 | | 2y^2-3y=-4 | | 2y^2-3y=4 | | 4a+10=8a+5 | | 0.5x-3+x=15 | | ln(x-1)+ln(x+5)=0 | | 6x^2=4-5x | | 5x+17=x-11 | | 3(h-6)=2(5-2h) | | 8x-12=4x | | 7y-3=4y+9 | | 2(x-1)=3x-1-x | | 4x+80=2x-20 | | 6.4T=64 | | (x^4)-(45*x^3)+(560*x^2)-(1380*x)+864=0 | | t^2=18 | | 7(3x+5)= | | 12X+78+8=13X+14 | | 4(4-4x)+1=2(x+2)-5x | | 4(p+3)=3-2-p | | 10m+11=4(2m+1)+3m | | 5y+11=5y+10 | | -x^2-2x+3=0 | | x^5+3x^4-5x^3+2x^2-7x+3=0 | | -7=-8Y+9 |